Institutional cross ownership of peer firms and investment sensitivity to stock price - CHO, Young Jun (Institutional Knowledge at Singapore Management University, 2020)
Theory suggests that stock price guides managers in corporate decisions as managers learn from price. We reason that cross-ownership of industry peers lowers information processing costs and increases industry specialization, helping investors better produce private information and transmit it to stock price. Cross-ownership can thus increase managerial learning. Consistent with our expectations, we find that a firm’s investment-q sensitivity increases as its cross-ownership increases. We strengthen the causal inference by conducting a difference-in-differences analysis using the 2003 mutual fund scandal. Overall, our results suggest that cross-ownership can induce more efficient corporate decisions by helping prices better reflect investors’ private information.